Intraoperative neurophysiological monitoring during urgent surgical extracranial internal carotid artery recanalization. (June 2022) - Ostrý, Svatopluk; Nevšímal, Milan; Reiser, Martin; Voldřich, Richard; Krtička, Ondřej; Kubále, Jiří; Nevšímalová, Miroslava; Fiedler, Jiří
Highlights: Intraoperative ischemia during urgent internal carotid artery recanalization is preventable by selective shunting. Selective shunting based on intraoperative somatosensory evoked potentials may prevent intraoperative ischemia development. Intraoperative monitoring may contribute to improving of clinical outcome after urgent internal carotid artery recanalization. Abstract: Objective: The clinical outcome of surgical extracranial internal carotid artery (eICA) recanalization may be adversely affected by intraoperative ischemia. Median nerve somatosensory evoked potential (SEP) amplitude correlates well with cerebral blood flow. Our study presents the value of intraoperative SEP and selective shunting in the prevention of intraoperative ischemia development during urgent eICA recanalization. Methods: Prospective recruitment of patients with acute unilateral eICA occlusion. All underwent surgical recanalization with intraoperative monitoring of scalp median SEPs. Preoperative clinical findings, cerebral collaterals, and 3 month functional outcome were evaluated. Results: The cohort consisted of 33 patients. Intraoperative SEP amplitude decreased significantly in 6 (18.2%). An intraluminal shunt was inserted twice (6.1%), surgical complications occurred in 6 (18.2%), intracerebral hemorrhage was not found. Favorable outcome 3 months after surgery according to the modified Rankin scale (mRS 0–2) was achieved in 28 (84.8%), 3 patients died (9.1%). Conclusions: Intraoperative SEP during urgent eICA recanalization seems to be beneficial. Thanks to the effective measure based on the intraoperative SEP changes, the clinical outcome in four (12.1%) could be positively affected. Significance: The results suggest that selective shunting based on intraoperative median SEPs may prevent intraoperative ischemia and may improve overall outcome of urgent eICA recanalization.